Education Planning and Its Implications for Education Policy during the Covid-19 Pandemic - Ismail, Feiby; Pawero, Abdul Muis Daeng; Umar, Mardan (Universitas Malikussaleh, 2021)
Indonesian education during the Covid-19 era entered a different situation. The real situation has long been predicted by technology experts that all areas of life will enter the realm of digital technology-based activities, including education. For this reason, education in Indonesia must be able to find new directions for education in formulating policies to be taken. One of the important things that must be prepared is at the education planning level. The problem that needs to be studied is how educational institutions formulate educational program planning during the Covid-19 pandemic while maintaining the quality of education. Educational planning carried out by educational institutions must reflect the existence of a vision, mission, goals and work plans, as raw materials or a reference for educational policies at the managerial level. This paper will discuss the education planning process in terms of its implications for quality-oriented education policy during a pandemic.